การฟอกเงิน : ศึกษาเปรียบเทียบกฎหมายไทยกับอนุสัญญาสหประชาชาติว่าด้วยการต่อต้านองค์กรอาชญากรรมข้ามชาติ - ชัยรัตน์ ศักดิ์โกศล (จุฬาลงกรณ์มหาวิทยาลัย, 2001)
Under the globalization, the crime formation has changed and developed from acting within a country by a single criminal into proceeding by a transnational organized crime under the profit objective same as other general transnational businesses. A lot of proceeds of crime or dirty money has affected to the country s economic, social and political systems broadly when it enters to the financial system; so that, law measures should eradicate this dirty money or at least protect the utilization from the dirty money in carrying out unlawful businesses or other activities. This mentioned idea is the principle of money laundering law as a part of the law measure in criminal suppressing. The world community has realized the threat from transnational organized crime and money laundering, including the difficult for government officers to force laws efficiently for transnational organized crime, then enacted jointly the United Nations convention against transnational organized crime 2000 which Thailand has signed in this convention already under the responsibility to adapt our laws being consistent with this convention. Therefore, the question is whether or how the money laundering control act B.E. 2542 is enough to support as a conventional obligation. The result indicates that most of Thailand law measures concerning with money laundering is consistent with this convention but some is different or unclear especially 7 category fundamental penalty as the money laundering control act B.E. 2542 less than as this convention. Thus to extent the scope of law application and be consistent with this convention, the money laundering control act B.E. 2542 with article 3 should be added that "(8) the penalty as enacted inthe law protecting and combating against transnational organized crime ........" However, the suitable law measures can disappear dirty money from the country s financial system and the circulation of financial flow will proceed accurately as economic cycle and be stable.